Endoscopic investigation in non-iron deficiency anemia: a cost to the health system without patient benefit - Mogilevski, Tamara; Smith, Rebecca; Johnson, Douglas; Charles, Patrick G. P.; Churilov, Leonid; Vaughan, Rhys; Ma, Ronald; Testro, Adam (Endoscopy International Open, 2016)
Background and aims: The indication for endoscopy to investigate anemia of causes other than iron deficiency is not clear. Increasing numbers of endoscopic procedures for anemia raises concerns about costs to the health system, waiting times, and patient safety. The primary aim of this study was to determine the diagnostic yield of endoscopy in patients referred to undergo investigation for anemia. Secondary aims were to identify additional factors enabling the risk stratification of those likely to benefit from endoscopic investigation, and to undertake a cost analysis of performing endoscopy in this group of patients.Methods: We performed a retrospective review of endoscopy referrals for the investigation of anemia over a 12-month period at a single center. The patients were divided into three groups: those who had true iron deficiency anemia (IDA), tissue iron deficiency without anemia (TIDWA), or anemia of other cause (AOC). Outcome measures included finding a lesion responsible for the anemia and a significant change of management as a result of endoscopy. A costing analysis was performed with an activity-based costing method.Results: We identified 283 patients who underwent endoscopy to investigate anemia. A likely cause of anemia was found in 31 of 150 patients with IDA (21 %) and 0 patients in the other categories (P < 0.001). A change of management was observed in 35 patients with IDA (23 %), 1 of 14 patients with TIDWA (7.14 %), and 8 of 119 patients with AOC (6.7 %) (P < 0.001). The cost of a single colonoscopy or gastroscopy was approximated to be $ 2209.Conclusions: Endoscopic investigation for non-IDA comes at a significant cost to our institution, equating to a minimum of $ 293 797 per annum in extra costs, and does not result in a change of management in the majority of patients. No additional factors could be established to identify patients who might be more likely to benefit from endoscopic investigation. The endoscopic investigation of non-IDA should be minimized.